2022
DOI: 10.3389/fpsyt.2021.745034
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Maternal Psychological Wellbeing During the Malaysian Movement Control Order: A Cross-Sectional Study

Abstract: Background: COVID-19 pandemic had resulted in nationwide lockdown as a disease control measure. Potential harm to self and baby due to COVID-19 infection as well as uncertainties about delivery are among contributors to maternal anxiety. We aimed to assess the prevalence of psychological distress among pregnant women during the Malaysian Movement Control Order (MCO).Methods: A cross-sectional study was conducted between May and June 2020 in a teaching hospital in Kuala Lumpur, Malaysia. A self-administered ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Generalized anxiety disorder (including anxiety not specified) was the most commonly reported anxiety disorder, examined by 184 of 203 studies (90.6%) . The pooled point prevalence for generalized anxiety disorder was 22.2% (95% CI, 19.4%-25.0%; n = 173 553).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized anxiety disorder (including anxiety not specified) was the most commonly reported anxiety disorder, examined by 184 of 203 studies (90.6%) . The pooled point prevalence for generalized anxiety disorder was 22.2% (95% CI, 19.4%-25.0%; n = 173 553).…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 10 617 studies; 1231 full texts were reviewed, and of these, 203 studies were included (Figure 1; eTable 2 in Supplement 1). Cumulatively, outcomes were reported for 212 318 perinatal women (from conception to 12 months post birth) from 33 LMICs. The prevalence estimates of 6 anxiety and related disorders were reported: generalized anxiety disorder, social anxiety disorder, posttraumatic stress disorder, obsessive-compulsive disorder, panic disorder, and adjustment disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Our recently published data indicate that over four-fifths of our obstetric patients expressed worry about the risk of COVID-19 infection to themselves and their babies (21). A study among pregnant individuals in Singapore during the early wave of the pandemic demonstrated that women who associated COVID-19 infection with fetal anomalies and intrauterine fetal death had significantly higher anxiety scores (41).…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire consists of five items that evaluate maternal anxiety concerning COVID-19 infection to self and baby as well as pregnancy complications such as miscarriage, fetal anomaly, and preterm birth. This questionnaire demonstrated good internal consistency with Cronbach's alpha of 0.928 (21). The total score ranged between 5 to 25, and a 50% cut-off level (score ≥13) indicates greater maternal anxiety.…”
Section: Covid-pregnancy-related Anxietymentioning
confidence: 95%
See 1 more Smart Citation